(untitled) (Reflection and Critique Law Magazine, 2025)
This paper addresses the limits of the use of Artificial Intelligence (AI) within the scope of Criminal Law, analyzing its application in line with the principles laid down in the Federal Constitution and the Brazilian Criminal Code, such as the principle of due process of law and the individualization of punishment, as well as the rights guaranteed in the Inter-American Convention on Human Rights, to which Brazil is a signatory. This raises the question: is it feasible to use the tools that come from Artificial Intelligence within the scope of Brazilian Criminal Law? It is necessary to ask whether these technologies are effective for neutral and objective decision-making, recognizing that they are important tools to help relieve the burden on the Brazilian judicial system. The research is based on the need to investigate whether the use of Artificial Intelligence in the jurisdictional and procedural context of Brazilian Criminal Law is in line with the necessary respect for individual constitutional guarantees. The methodology used will be a qualitative approach combining bibliographical and documentary research, with analysis of legislation and practical cases.